A STUDY ON THE CHOREOGRAPHY OF THE NGAJAT PINGAI DANCE OF THE MELABAN DAYAK SUB-TRIBE COMMUNITY IN BINDA DUSUN KETUNGAU TENGAH DISTRICT, SINTANG DISTRICT - Lestari, Friska (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this research is to identify and describe the process of and the from of choreography in Tari Ngajat Pingai. The main problem in research this is how the process and from of choreography in Choreography Study Tari Ngajat Pingai. Researchers use qualitative research methods that produce descriptive data with a coreographic approach. Collection techniques the data used are observation, interview and documentation techniques. The results of the research on the Choreography Study Tari Ngajat Pingai that have been processed and packaged by Temenggung Empuyu relate to the process and form of the choreography. The choreography process includes exploration, improvisation and composition. The exploration process in question is the process of finding and digging an object. The improvisation process in question is the process of trying based on the exploration process that has been done previously. The composition process in question is the process of composing and organizing that has been carried out in the exploration and improvisation process. The choreographic from includes motion, dance space and floor design, dance accompaniment, make-up dan clothing and dance properties. Tari Ngajat Pingai movements are divided into three, namely the variety of opening movements, the variety of core movements and variety of closing movements. Dance space at the Tari Ngajat Pingai performance can be performed in various spaces, such as a closed or open stage and floor design used is a straight line design (horizontal and vertical), a curved line design, a V design and a W design. Tari Ngajat Pingai accompaniment uses several musical instruments, such as a tawak or gong, ketebung or gendang and engkerumong or kenong. The make-up used is beautiful make-up and clothes used by female dancers in Tari Ngajat Pingai, namely kutang as a top and kain bulus tating as skrit subordinates as well as accessories such as a tusuk sangul ketip, tengak cekak, tengak panjai, sumping dan sementing ntui. The property used is piring.